2014
DOI: 10.4103/0972-124x.128194
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between chronic periodontitis and anemia: A 6-month follow-up study

Abstract: Background:In India, anemia is a common and serious health disorder among both sexes and all age groups, with anemia of chronic disease (ACD) being the second most prevalent anemia. Periodontitis is an inflammatory disease of the supporting tissues of the tooth caused by specific microorganisms. An immune response to bacteria and their products induces a major vascular response, offering explanatory mechanisms for the interactions between periodontal infection and a variety of systemic disorders. Therefore, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
(39 reference statements)
4
18
1
3
Order By: Relevance
“…In the group of individuals with chronic periodontitis, both hematocrit values and those of serum iron were lower than in participants without periodontitis. The lowest hematocrit value in this group can be attributed to less number of red blood cells in individuals with periodontal infection, according to the results of previous studies (Kolte et al, 2014;Patel et al, 2014). Small serum iron values in participants with periodontitis were observed, reinforcing the character of anemia of chronic disease, and consequent blocking of intracellular iron release.…”
Section: Dear Editorsupporting
confidence: 76%
“…In the group of individuals with chronic periodontitis, both hematocrit values and those of serum iron were lower than in participants without periodontitis. The lowest hematocrit value in this group can be attributed to less number of red blood cells in individuals with periodontal infection, according to the results of previous studies (Kolte et al, 2014;Patel et al, 2014). Small serum iron values in participants with periodontitis were observed, reinforcing the character of anemia of chronic disease, and consequent blocking of intracellular iron release.…”
Section: Dear Editorsupporting
confidence: 76%
“…Hb, RBC counts, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular Hb (MCH), mean corpuscular Hb concentration (MCHC), and erythrocyte sedimentation rate (ESR) (Hutter et al, 2001;Gokhale et al, 2010;Naik et al, 2010;Prakash et al, 2012;Chakraborty et al, 2014;Kolte et al, 2014;Patel et al, 2014;Khan et al, 2015;Latha et al, 2015;Anumolu et al, 2016;Carvalho et al, 2016;Nibal et al, 2019).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…It has recently been shown that diff erent chronic oral conditions such as periodontitis can be related to diff erent systemic diseases, e.g., anemia of chronic disease 40 . Posttransplant anemia is a chronic condition related to erythropoietin substitution and blood transfusion.…”
Section: Discussionmentioning
confidence: 99%